RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA BERBAGAI PERBANDINGAN MEDIA TANAM DI PRE NURSERY - Bastani Sepindjung; Ridwan Hanan; Ferry Andrian (JURNAL TRIAGRO, 2016)
Growth Responses of Oil Palm Seedlings (Elaeis guineensis Jacq.) Comparison Of The Various Growing Media in Pre nursery. The usefulness of this study are expected to be useful for science and technology, and can be used as a guide for people who want to plant oil palm trees. This research has been conducted in the field nursery PT. Mahkota Andalan Sawit at Pedu Village, district Jejawi, Region Ogan Komering Ilir, starting from June 2014 to September 2014 This study used a randomized block design experiment method (RAK) which consisted of 4 treatments and each treatment was repeated 6 times. The treatment under study P1 = 100% top soil (Without Peat soil mix), P2 = 75% top soil and 25% peat soil, P3 = 50% top soil and 50% peat soil, P4 = 25% top soil and 75% peat soil. Variables measured were plant height, stem girth, root fresh weight, root dry weight, number of roots, number of leaves and leaf area. Based on the results of the study showed that 25% of the soil planting medium top soil and 75% peat soils respond well to the growth of oil palm seedlings age 90 Hst with generating plant height, stem girth, root fresh weight, root dry weight and leaf area respectively - also was 25.59 cm; 3,02 cm; 1.40 g; 0.48 g and 1608.75 cm Ã‚Â². Keywords : Oil palm, growth, media and pre nursery